E-commerce adoption in ASEAN: Who and where? - Abu H. Ayob (Future Business Journal, 2021)
As an economic bloc, the Association of Southeast Asia Nations (ASEAN) aims to leverage the usage of e-commerce for the benefits of all: government, enterprises, and citizens of its member countries. However, each country varies greatly in terms of economic development and cultural factors, which explains the uneven level of e-commerce adoption in the region. This paper seeks to provide empirical evidence by integrating individual and country-level characteristics to profile e-commerce users in ASEAN. By analyzing multi-source data from 5870 individuals in six countries in 2017, the results reveal that e-commerce adoption is more prevalent among female, younger, more educated, employed, and higher income users. Also, the adoption of e-commerce is found to be stronger in societies that exhibit high individualism, low masculinity and low uncertainty avoidance. This study proposes that e-commerce adoption shall not only be explained by individual characteristics and formal institutions, but also by country-level variables and national culture.
Keywords: 650; ASEAN; E-commerce adoption; Individual demographics; National culture